Chauri Chaura Revolution: A Review: चौरी चौरा की क्रान्ति: एक पुनरावलोकन - Poonam; Kumar, Pintu (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
The freedom struggle of any country is the greatest treasure of that country. The incidents that happened during this period and the martyrdom of the revolutionaries in them always serve as a source of inspiration for the people of that country. The Chauri Chaura incident that happened during the Indian freedom movement was also one such incident. This incident not only forced Gandhiji to withdraw the much talked about non-cooperation movement of that time but also gave a new direction and condition to the national movement. This incident happened on 4 February 1922 at a place called Chauri Chaura in Gorakhpur district of the then United Province (presently Uttar Pradesh) during the program of the non-cooperation movement, where an angry mob set a police station on fire in which a total of 23 people including 22 policemen and 1 inspector were killed. Abstract in Hindi Language: किसी भी देश का स्वतंत्रता संग्राम उस देश की सर्वोच्च निधि होती है। इस दौरान घटी घटनाएं एवं उनमे क्रांतिकारियों द्वारा दी गई शहादत उस देश के लोगों के लिए सदैव प्रेरणा स्रोत का कार्य करती है। भारतीय स्वतंत्रता आंदोलन के दौरान घटी चैरी चैरा की घटना भी एक ऐसी ही घटना थी। इस घटना ने न सिर्फ उस समय के बहुचर्चित असहयोग आंदोलन को वापस लेने के लिये गाँधी जी को विवश किया अपितु राष्ट्रीय आंदोलन को नई दिशा और दशा भी दे डाली। 4 फरवरी 1922 को असहयोग आंदोलन के कार्यक्रम के दौरान तत्कालीन संयुक्त प्रान्त (वर्तमान में उत्तर प्रदेश) के गोरखपुर जनपद में चैरी चैरा नामक स्थान पर यह घटना घटी थी, जहाँ आक्रोशित भीड़ ने एक थाने को आग लगा दी जिसमें कुल 22 पुलिसवाले और 1 दरोगा सहित कुल 23 लोग मारे गए। Keywords: भारत, स्वतंत्रता संग्राम, चैरी चैरा, असहयोग आंदोलन।